Multiple urinary bladder masses from metastatic prostate adenocarcinoma - Richard Choo; Robert C Miller; Vishal S. Chandan; Christopher Hallemeier; Manish Kohli (Rare Tumors, 2010)
We present an unusual case of metastatic prostate adenocarcinoma that manifested with multiple exophytic intravesical masses, mimicking a multifocal primary bladder tumor. Biopsy with immunohistochemical analysis confirmed metastatic prostate adenocarcinoma. The patient was treated palliatively with external beam radiotherapy to prevent possible symptoms from local tumor progression. This case illustrates that when a patient with known prostate cancer presents with multifocal bladder tumors, the possibility of metastatic prostate cancer should be considered.